Eye Gaze Patterns of Decision Process in Prosocial Behavior - Peshkovskaya, Anastasia; Myagkov, Mikhail (Frontiers in Behavioral Neuroscience, 2020)
Understanding human behavior remains a grand challenge across disciplines. We used eye tracking to investigate how visual perception associated with a strategic behavior in decision process. Gaze activity and eye movement patterns were measured in fourteen human participants with different decision strategies. We also employed a social domain to force strategic behavior. We found that social interaction significantly improves level of cooperation, prosocial decisions, and overall cooperative strategy in experiment participants. Gaze behavior in individuals with cooperative strategy characterized by a greater number of fixations and frequent gaze returns to the scanned areas. Contrary, individuals with non-cooperative strategy approached decision-making task stimuli in a distinct way, with long duration fixations, and a low number of gaze returns to the areas already scanned. Social domain, which enhances cooperation and prosocial behavior, made participants more attentive to the task stimuli in our experiments. Moreover, prolonged gaze at the area of cooperative choice testified in favor of the cooperative decision.